Physical Chemistry of Cold Gas-Phase Functional Molecules and Clusters - Ebata, Takayuki; Fujii, Masaaki; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book describes advanced research on the structures and photochemical properties of polyatomic molecules and molecular clusters having various functionalities under cold gas-phase conditions. Target molecules are crown ethers, polypeptides, large size protonated clusters, metal clusters, and other complex polyatomic molecules of special interest. A variety of advanced frequency and time-domain laser spectroscopic methods are applied. The book begins with the principle of an experimental setup for cold gas-phase molecules and various laser spectroscopic methods, followed by chapters on investigation of specific molecular systems. Through a molecular-level approach and analysis by quantum chemical calculation, it is possible to learn how atomic and molecular-level interactions (van der Waals, hydrogen-bonding, and others) control the specific properties of molecules and clusters. Those properties include molecular recognition, induced fitting, chirality, proton and hydrogen transfer,isomerization, and catalytic reaction. The information will be applicable to the design of new types of functional molecules and nanoparticles in the broad area that includes applied chemistry, drug delivery systems, and catalysts.
1. Experimental Methods: Generation of cold gas-phase molecules, molecular ions, their clusters, metal clusters, and laser spectroscopy -- 2. Microscopic Study on Molecular Recognition of Host-guest Complexes between Crown Ethers and Aromatic Molecules -- 3. Chirality Effects in Jet-cooled Cyclic Dipeptides -- 4. Hydrogen Bond Networks Formed by Several Dozens to Hundreds of Molecules in the Gas-Phase -- 5. Gas-Phase Spectroscopy of Metal Ion-Benzo-Crown Ether Complexes -- 6. Metal Cation Coordination and Solvation Studied with Infrared Spectroscopy in the Gas Phase -- 7. Superatomic Nanoclusters Comprising Silicon or Aluminum Cages -- 8. Characterization of Chemically Modified Gold/Silver Superatoms in the Gas Phase -- 9. Time-resolved Study on Vibrational Energy Relaxation of Aromatic Molecules and Their Clusters in the Gas Phase -- 10. Non-adiabatic Dynamics of Molecules Studied Using Vacuum-ultraviolet Ultrafast Photoelectron Spectroscopy -- 11. Femtosecond Time-resolved Photoelectron Spectroscopy of Molecular Anions -- 12. Excited States Processes in Protonated Molecules Studied by Frequency-domain Spectroscopy -- 13. Time-resolved Study on Photo-initiated Isomerization of Clusters.
Keywords: Physical chemistry; Spectrum analysis; Atomic structure .; Molecular structure .; Nanochemistry; Physical Chemistry; Spectroscopy; Atomic and Molecular Structure and Properties; Nanochemistry